Enantioselective Synthesis of Spirooxindoles: Asymmetric [3+2] Cycloaddition of (3‐Isothiocyanato)oxindoles with Azodicarboxylates. Issue 35 (8th November 2013) - Jiang, Yu; Pei, Cheng‐Kui; Du, Dan; Li, Xiao‐Ge; He, Ya‐Nan; Xu, Qin; Shi, Min
Abstract: The catalytic asymmetric [3+2] cycloaddition of (3‐isothiocyanato)oxindoles with azodicarboxylates has been explored in the presence of (DHQD)2 PHAL. It affords spirooxindoles having two heterocycles at their C3′‐position in excellent yields, with high enantioselectivities, and under mild conditions within 5 min. Moreover, another spirooxindole derived from the reaction of (3‐isothiocyanato)oxindole with two molecules of azodicarboxylate could also be formed in excellent yields with the same high enantioselectivities under the standard conditions. Abstract : The catalytic asymmetric [3+2] cycloaddition of (3‐isothiocyanato)oxindoles with azodicarboxylates in the presence of (DHQD)2 PHAL affords spirooxindoles having two heterocycles at their C3′‐position in excellent yields, with high enantioselectivities, and under mild conditions.